Mobile APP UI/UX Design Overcomes Masturbation Addiction - Mukhamat Andi Setiawan; Poerbaningtyas Evy; Adita Kusumasari Kusumasari (IC-ITECHS, 2022)
Teenagers develop a variety of interests during this time, including a sexual one that might result in a masturbation addiction. As a remedy to this problem, the researcher created a UI/UX application design to combat mobile-based masturbation addiction. Through a mobile application, this design seeks to assist youths who are masturbation dependent. The research method used in this study is qualitative. Researchers utilize design thinking to create their applications, and there are five processes that : empathize, define, ideate, prototype, and testing. Data was gathered through in-depth interviews, questionnaires, and software design. The end result of this design is an Mastopbasi application interface with three key features: Daily Reports, Professional Assistance, and Productivity. Each of these features has a specific purpose and performs a certain function based on user requirements. Suggestions for an interface design must be based on the demands of the target audience. In the hope that they will be able to fix the problem, this will heighten interest in the product and provide customers the option to select a product that best matchestheir needs.